2008
DOI: 10.1152/jn.01043.2007
|View full text |Cite
|
Sign up to set email alerts
|

Substantia Nigra Stimulation Influences Monkey Superior Colliculus Neuronal Activity Bilaterally

Abstract: Liu P, Basso MA. Substantia nigra stimulation influences monkey superior colliculus neuronal activity bilaterally. J Neurophysiol 100: 1098 -1112, 2008. First published June 25, 2008 doi:10.1152/jn.01043.2007. The inhibitory drive arising from the basal ganglia is thought to prevent the occurrence of orienting movements of the eyes, head, and body in monkeys and other mammals. The direct projection from the substantia nigra pars reticulata (SNr) to the superior colliculus (SC) mediates the inhibition. Since th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 90 publications
5
59
0
Order By: Relevance
“…Likewise, recent studies have demonstrated that the substantia nigra pars reticulata (SNr), in addition to its well-known inhibitory projection to the ipsilateral SC (Chevalier et al 1984;Hikosaka and Wurtz 1983;Karabelas and Moschovakis 1985;May and Hall 1984), provides a crossed inhibitory input to the opposite SC Liu and Basso 2008). Critically, these SNr projections perform complementary functions, simultaneously facilitating contralateral stimulus/movement representations (via disinhibition) while suppressing those to the ipsilateral side.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, recent studies have demonstrated that the substantia nigra pars reticulata (SNr), in addition to its well-known inhibitory projection to the ipsilateral SC (Chevalier et al 1984;Hikosaka and Wurtz 1983;Karabelas and Moschovakis 1985;May and Hall 1984), provides a crossed inhibitory input to the opposite SC Liu and Basso 2008). Critically, these SNr projections perform complementary functions, simultaneously facilitating contralateral stimulus/movement representations (via disinhibition) while suppressing those to the ipsilateral side.…”
Section: Discussionmentioning
confidence: 99%
“…A second set of studies suggesting a broader role for SNr input to the SC examined the anatomy and physiology of this input. First, while the disinhibition model is based on ipsilaterally projecting (i.e., "uncrossed") nigrotectal neurons, some ("crossed") nigrotectal neurons project contralaterally (Beckstead et al 1981;Chevalier et al 1981;Deniau et al 1977;Gerfen et al 1982;Jayaraman et al 1977;Liu and Basso 2008) and a small number project to both SCs (Cebrián et al 2005). Given that crossed nigrotectal projections are also inhibitory, they would appear to promote movements ipsiversive to the phasically inactivated SNr, inconsistent with the disinhibition model.…”
Section: Gabaergic Input To Superior Colliculus From Substantia Nigramentioning
confidence: 99%
“…Given that crossed nigrotectal projections are also inhibitory, they would appear to promote movements ipsiversive to the phasically inactivated SNr, inconsistent with the disinhibition model. Second, in addition to the influence of SNr activity on bursting SC neurons that initiate movements (Hikosaka and Wurtz 1983), SNr input modulates the activity of buildup SC neurons (Liu and Basso 2008) thought to subserve the selection of targets for movement (but see Corneil et al 2007). Finally, uncrossed nigrotectal neurons project to GABAergic SC neurons-which, as discussed above, may mediate the inhibition between SC circuits representing competing movements-as often as they project to glutamatergic SC neurons (Kaneda et al 2008), further suggesting a broader role for the SNr than simple disinhibition.…”
Section: Gabaergic Input To Superior Colliculus From Substantia Nigramentioning
confidence: 99%
“…Through local excitation, this differential activation could get amplified and gradually lead to elevated firing rates until a movement is triggered. Alternately, modulation of inhibitory input (e.g., from substantia nigra; Hikosaka and Wurtz 1985;Isa and Hall 2009;Liu and Basso 2008) or excitatory input (e.g., from the prefrontal cortex; Sommer and Wurtz 2000;Wurtz et al 2001) could shape SC population activity and contribute to microsaccade-related buildup. These mechanisms are sources of saccade-related buildup of activity elsewhere in the SC, highlighting the similarity between microsaccades and saccades at the mechanistic level.…”
Section: Neural Control Of Microsaccadesmentioning
confidence: 99%